Morphological identification of the patterns of prostatic intraepithelial neoplasia and their importance. Issue 9 (1st September 2000) - Montironi, Rodolfo; Mazzucchelli, Roberta; Algaba, Ferran; Lopez-Beltran, Antonio
Abstract : High grade prostatic intraepithelial neoplasia (PIN) is the most likely precursor of prostatic carcinoma. PIN has a high predictive value as a marker for carcinoma, and its identification in biopsy specimens warrants repeat biopsy for concurrent or subsequent carcinoma. The only methods of detection are biopsy and transurethral resection; PIN does not greatly raise the concentration of serum prostate specific antigen (PSA) or its derivatives, does not induce a palpable mass, and cannot be detected by ultrasound. Androgen deprivation decreases the prevalence and extent of PIN, suggesting that this form of treatment might play a role in chemoprevention. Radiotherapy is also associated with a decreased incidence of PIN.